2014
DOI: 10.1038/srep04136
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE:Type IV collagen α1-chain noncollagenous domain blocks MMP-2 activation both in-vitro and in-vivo

Abstract: α1(IV)NC1 inhibits angiogenesis by regulating MAPK activation, this biological function was partly attributed α1(IV)NC1 binding to α1β1-integrin. However, its potent antiangiogenic activity and the molecular targets of α1(IV)NC1 has not been investigated. In the present study, the regulation of MMP-2 activation by α1(IV)NC1 was evaluated. α1β1-integrin which is required for inhibition of angiogenesis is not playing a role in cellular invasion and inhibition of MMP-2 activation by α1(IV)NC1. We found that α1(IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…It was first reported that metalloproteinase 9 (MMP‐9) might cleave collagen α3(IV) chain to release NC1 (non‐collagenous 1) domain, a 28‐kDa peptide, from its C‐terminus in the rat testis via proteolysis . This NC1‐peptide has also been shown to be a biologically active peptide, capable of modulating a number of cellular functions including MMP activation, cell adhesion, angiogenesis, tumorigenesis, and others based on studies in multiple endothelia and/or epithelia . Studies have shown that NC1‐peptide was also generated in the testis, capable of modulating Sertoli cell tight junction (TJ)‐permeability barrier function, and its cloning into the mammalian expression vector pCI‐neo to be used for its overexpression in Sertoli cells in vitro as well as in the testis in vivo was shown to perturb the Sertoli cell BTB function both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first reported that metalloproteinase 9 (MMP‐9) might cleave collagen α3(IV) chain to release NC1 (non‐collagenous 1) domain, a 28‐kDa peptide, from its C‐terminus in the rat testis via proteolysis . This NC1‐peptide has also been shown to be a biologically active peptide, capable of modulating a number of cellular functions including MMP activation, cell adhesion, angiogenesis, tumorigenesis, and others based on studies in multiple endothelia and/or epithelia . Studies have shown that NC1‐peptide was also generated in the testis, capable of modulating Sertoli cell tight junction (TJ)‐permeability barrier function, and its cloning into the mammalian expression vector pCI‐neo to be used for its overexpression in Sertoli cells in vitro as well as in the testis in vivo was shown to perturb the Sertoli cell BTB function both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…9 This NC1-peptide has also been shown to be a biologically active peptide, capable of modulating a number of cellular functions including MMP activation, cell adhesion, angiogenesis, tumorigenesis, and others based on studies in multiple endothelia and/or epithelia. [10][11][12][13] Studies have shown that NC1-peptide was also generated in the testis, capable of modulating Sertoli cell tight junction (TJ)-permeability barrier function, 14 and its cloning into the mammalian expression vector pCI-neo to be used for its overexpression in Sertoli cells in vitro as well as in the testis in vivo was shown to perturb the Sertoli cell BTB function both in vitro and in vivo. 15 These studies thus illustrate that the NC1-peptide exerts its modulating effects to support spermatogenesis are mediated through changes in the cytoskeletal organization of both actin-and MT-cytoskeletons, in particular the organization of actin filament bundles and MTs across the Sertoli cell at the ultrastructures known as the basal ectoplasmic specialization (ES) or apical ES at the Sertoli cell-cell or Sertoli-spermatid interface, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…MMP´s can be activated by removal of the N-terminal pro-domain. They are inactivated via interaction with Tissue Inhibitors Of Matrix Metalloproteinases (TIMP`s) [10] [11] [3] [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The proportion of pro-MMP-2, TIMP-2 and MT1-MMP is an important factor for the regulation of pro-MMP-2 activation and the expression of MMP-2 and TIMP-2 is connected to each other. [13] [14] [15] [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are known to play a critical role in tumour progression, invasiveness, and metastasis 27 and are promising tumour biomarkers overexpressed in most cancers 28 . MMPs degrade collagen type IV and further enable the escape of cancer cells to other organs 29 . Additionally, MMP probes have been shown to decrease the incidence of positive margins and increase tumour-free survival after dissections.…”
mentioning
confidence: 99%